253 Impact of Corn Hybrid Selection for Fiber and Starch Traits on in Vivo Nutrient Digestion in Beef Cattle. (7th May 2021) - Xiong, Jiehua; Norman, Mitch; Wilson, Hannah; Crabtree, Caleb; Erickson, Galen E
Abstract: Evaluation of corn silage digestibility is normally done using laboratory techniques to predict the performance if fed to cattle, which may or may not predict actual performance when fed to cattle. The objective of this study was to evaluate two Masters Choice corn silage hybrids previously selected for improved fiber and starch digestion on nutrient intake and digestion in cattle. In a 126-day digestion study, six ruminally fistulated beef steers were utilized in a 3×6 Latin rectangle design with three dietary treatments and six periods (21 days in length with 14 days of adaptation and 7 days of collection). Diets consisted of 80% corn silage (dry matter basis) of Masters Choice hybrid MCT6365 RIB (MC1; selected for greater fiber and starch digestion) and MCT6733 GT3000 (MC2; older hybrid selected for greater fiber digestion) and were compared to a conventional corn hybrid (CON; commonly grown in Eastern Nebraska). The remainder of the diet included 15% modified distillers grains plus solubles and 5% supplement. Corn silage hybrid did not impact dry matter or organic matter (OM) intake (P ≥ 0.68), but hybrid treatment impacted OM, starch, and energy digestibility (P < 0.02). Steers fed MC1 corn silage had greater (P < 0.01) total tract OM and energy digestibility, as well as digestible energy (DE, P = 0.02) content of the diet when compared to MC2, with steers fed CON being intermediate (P ≥ 0.09). Feeding MC1 also resulted in greater (P = 0.03) total tract starch digestibility than MC2, with no difference (P = 0.12) when compared to CON. Results indicated that feeding MC1 corn silage improved digestion and energy availability to the steers, which allowed for greater average daily gain and improved feed efficiency observed in the corresponding growing trial, while the opposite was true for MC2.